Oral Immunization of Chickens With Recombinant Lactobacillus plantarum Vaccine Against Early ALV-J Infection - Wang, Shenghua; Geng, Na; Zhou, Dong; Qu, Yi; Shi, Mengke; Xu, Yuliang; Liu, Kangping; Liu, Yongxia; Liu, Jianzhu (Frontiers in Immunology, 2019)
In this study, a novel oral vaccine of recombinant lactobacillus plantarum (L.plantarum) containing gp85 protein was explored and its effects were assessed in order to exploit an optimized vaccine for prevention of subgroup J Avian Leukosis Virus (ALV-J) infection. The gp85 protein of ALV-J was expressed on the surface of L.plantarum with the surface-display motif, pgsA, by constructing a shuttle vector pMG36e:pgsA:gp85. Surface localization of the fusion protein was verified by western blot and flow cytometry. Then Specific Pathogen Free (SPF) Hy-Line Brown layer chickens were orally vaccinated with the recombinant L.plantarum and presented with high levels of serum immunoglobulin G (IgG) and secretory immunoglobulin A (sIgA) titers in bile and duodenal-mucosal fluid. After challenged with ALV-J of a 3×103 50% tissue culture infective dose (TCID50), serum samples of the chickens were collected and viremia were analyzed. Results showed that, compared to the L.plantarum and PBS control group, the recombinant L.plantarum group rise significantly after inoculation in antibody levels, and provide better protection against ALV-J from viremia detection. These results indicate that oral immunization with the recombinant L.plantarum provides an effective means for eliciting protective immune response against early ALV-J infection.